Recent Advances in Backward Stochastics Riccati Equations and Their Applications - Michael Kohlmann; Shanjian Tang (University of Konstanz, Center of Finance and Econometrics (CoFE), 2000)
The following backward stochastic Riccati differential equation (BSRDE in short) is motivated, and is then studied. Some properties are presented. The existence and uniqueness of a global adapted solution to a BSRDE has been open for the case D i 6= 0 for more than two decades. Our recent results on this topic are summarized. Finally, applications are addressed, both in finance and control.
urn:nbn:de:bsz:352-opus-5805
Keywords: 330; Kontrolltheorie; Stochastischer Prozess; Optionspreistheorie; Hedging; Theorie